The first well-documented record of the vine bud moth Theresimima ampellophaga (Bayle-Barelle, 1808) in Albania established by field screening of sex pheromone and sex attractant traps (Lepidoptera: Zygaenidae, Procridinae) - V. Verenozi; T. B. Toshova; K. A. Efetov; E. E. Kucherenko; A. Rredhi; G. M. Tarmann (SHILAP)
The vine bud moth, Theresimima ampellophaga (Bayle-Barelle, 1808), has been known as a pest on grapevine (Vitis vinifera) since ancient Roman times. Despite the fact that the vineyards are widely distributed in Albania, there are no clearly documented data about the presence of this species in this country. Delta sticky traps baited with the synthetic sex pheromone of Th. ampellophaga, (2R)-butyl (7Z)-tetradecenoate or the sex attractant EFETOV-2 (the racemic mixture of (2R)-butyl 2-dodecenoate and (2S)-butyl 2-dodecenoate) were used in eight vineyards in Albania for possible detection of the occurence of the vine bud moth. As a result, this species was recorded for the first time in Albania in four vineyards of three different municipalities: Fier (Apolloni), Konispol (Qafë Botë and Xarrë), and Vlorë (Panaja). The results showed a low population density of Th. ampellophaga in the southern and southwestern part of the country. Male moths were caught from the end of June - beginning of July and at the beginning of September indicating the presence of two generations of Th. ampellophaga in Albania.